THE INFLUENCE OF DIMENSION PARTICIPATORY LEADERSHIP ON JOB SATISFACTION AND EMPLOYEE PERFORMANCE - Tehubijuluw Zacharias; Risnawati Risnawati; Yandri Luturmas; Cliffard Manoppo (JURNAL BADATI, 2022)
Abstract: This study aims to analyze the influence of dimension of participatory Â leadership on job satisfaction and employee performance in the economic section of the Regional Secretariat of the East Seram Regency. The design of this study is descriptive and causal. The population of this study consisted of all employees of the Regional Secretariat of the East Seram Regency, namely 98 people. The sampling technique in this study was a saturated sample. Analysis of the data used is path analysis (path analysis) with the help of SPSS software. The results of the study show that (1) democratic leadership, consultative leadership and delegative leadership directly influence employee job satisfaction; (2) job satisfaction has a direct effect on employee performance; (3) democratic leadership, consultative leadership and delegative leadership indirectly influence performance through job satisfaction.